Supervisi Penerapan Metode Ummi dalam Meningkatkan Kemampuan Membaca dan Menghafal Al-Qurân - Ruqoyyah, Ruqoyyah; Wasik, Wasik (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2023)
Implementing a learning method requires guidance and supervision. In many cases, teachers are often required to implement a new method without any guidance and supervision. There is one application of learning methods that provides guidance and supervision, namely the application of the Ummi learning method in improving the ability to read and memorize the Al-Qur'an. This is worth studying. For this reason, this research is aimed at revealing how to implement supervision activities by focusing on three things, namely: steps, techniques and factors inhibiting and supporting these supervision activities. The research was carried out in two locations: SMPN 1 Sampang and SDN 1 Dalpenang Sampang. This research uses a qualitative approach with data collection techniques: non-participant observation, in-depth interviews, and documentation of related sources. The research results obtained are first, the stages of implementing supervision in both institutions include daily, weekly and monthly supervision. Second, the technique for implementing Ummi method supervision in both institutions is in the form of individual and group techniques. Individual supervision techniques include class visits, individual meetings and document observation, while group techniques include school visits, evaluation meetings and teaching demonstrations. Third, the supporting factors for implementing the Ummi method of supervision in both institutions are support from school principals and parents who encourage supervisors to continue to supervise, supervisors' activeness and teacher welfare as well as adequate facilities. The inhibiting factors are the lack of supervision time and the lack of supervisors which is not commensurate with the number of existing groups. The results of the research have implications for supervisors being able to emphasize the objectives of supervision, so that supervision activities are not understood as a form of supervision but as mentoring and guidance activities.